2013
DOI: 10.1155/2013/437830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Two Oral Health Video Interventions with Early Head Start Families

Abstract: Poor oral health in early childhood can have long-term consequences, and parents often are unaware of the importance of preventive measures for infants and toddlers. Children in rural, low-income families suffer disproportionately from the effects of poor oral health. Participants were 91 parents of infants and toddlers enrolled in Early Head Start (EHS) living in rural Hawai'i, USA. In this quasi-experimental design, EHS home visitors were assigned to use either a didactic or family-centered video with parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…[2428, 32, 33, 35, 36, 39, 40] Four trials, however, were “quasi-experimental” with a pre-test/post-test design [20, 21, 34, and 37], two had equivalent [22, 29] and one had non-equivalent comparison group . [38] One included study was historically controlled non-randomized [23] and another was ecologic.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[2428, 32, 33, 35, 36, 39, 40] Four trials, however, were “quasi-experimental” with a pre-test/post-test design [20, 21, 34, and 37], two had equivalent [22, 29] and one had non-equivalent comparison group . [38] One included study was historically controlled non-randomized [23] and another was ecologic.…”
Section: Resultsmentioning
confidence: 99%
“…Seven home visiting programs [20, 23, 26&27, 36, 37, 38, 39] were reviewed as well whereas one intervention included both home visits and consultations at well-baby clinic. [22] Two studies [21, 38] reported including both urban and rural settings in their recruitment, five [23, 30, 34, 35, 37] were restricted to rural sites and three [25, 26, 28] to urbanized or metropolitan areas. Table 1 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations